Impact of Juvenile Diabetes Long-Term Treatment upon Adolescents Physical Activities at Al Nasiriya Diabetic and Endocrinology Center - Adil Ali Hussein1 , Khetam Mutasher Hatab2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Introduction: Exercise has a positive effect on health, strength gain, weight control, social activity and self development, contribute to the development of healthy habits in adults, but can also cause hypoglycemia. The variety, weight and duration of administration can cause various hormones (insulin, glucagon, catecholamine glucocorticoid), mediated metabolism. when the administration of insulin derived from insulin and / or an increase in anti-regulatory hormones increase glucose production in the liver and damage glucose in skeletal muscles. Although potential hyperglycemia can scare patients and their families, recipient fear of hypoglycemia can be a serious problem for clinical attention. Objectives: To determine impact of juvenile diabetes long-term treatment upon adolescents’ physical activity and to discovery out the relationship between impact of long-term treatment with adolescents specific demographic data. Methodology: A descriptive study design was performed to determine the impact of juvenile diabetes long-treatment upon adolescent’s physical activity in Al Nasiriya diabetic and endocrinology center. The study had started from February 6th, 2019 to June 7th, 2019. Non – probability (accidental) sample of (100) adolescents were selected. Conclusion: The present study concludes that the greatest impact of long-term treatment of diabetes on the adolescents lifestyle was on physical activity; in addition the statistical test shows that the significant association between the adolescents’ physical activity and their age, socio-economic status.